Implementasi Pilar Teori Organisasi Terhadap Pengelolaan Praktek Mandiri Perorangan - Ulfa Novirwan; Akbar Zein Al Ghozali; Purwadhi Purwadhi; Yani Restiani Widjaja (BADAN PENERBIT STIEPARI PRESS, 2025)
Individual practice management is one of the primary and secondary health care providers to achieve operational efficiency, coordination between human resources, and service quality. This article aims to analyze the implementation of the pillars of organizational theory on the management of individual independent practices using a multidimensional approach. This theory examines the division of labor, work grouping, hierarchy, and coordination of individual independent practices as health services. This theory provides recommendations for optimizing the four pillars of holistic organizational theory.